Peculiar All-Metal σ-Aromaticity of the [Au2Sb16]4− Anion in the Solid State - Popov, Ivan A.; Pan, Fu-Xing; You, Xue-Rui; Li, Lei-Jiao; Matito, Eduard; Liu, Chao; Zhai, Hua-Jin; Sun, Zhong-Ming; Boldyrev, Alexander I. (Angewandte Chemie International Edition, 2016)
Gas‐phase clusters are deemed to be σ‐aromatic when they satisfy the 4n+2 rule of aromaticity for delocalized σ electrons and fulfill other requirements known for aromatic systems. While the range of n values was shown to be quite broad when applied to short‐lived clusters found in molecular‐beam experiments, stability of all‐metal cluster‐like fragments isolated in condensed phase was previously shown to be mainly ascribed to two electrons (n=0). In this work, the applicability of this concept is extended towards solid‐state compounds by demonstrating a unique example of a storable compound, which was isolated as a stable [K([2.2.2]crypt)]+ salt, featuring a [Au2Sb16]4− cluster core possessing two all‐metal aromatic AuSb4 fragments with six delocalized σ electrons each (n=1). This discovery pushes the boundaries of the original idea of Kekulé and firmly establishes the usefulness of the σ‐aromaticity concept as a general idea for both small clusters and solid‐state compounds. A unique [Au2Sb16]4− complex was isolated as a stable salt and characterized by single‐crystal X‐ray diffraction. Its rod‐like Sb16 framework is the largest unfragmented Sbn polyanion isolated from solution, which was possible due to the σ‐aromatic stabilization through quenching with two Au atoms. The [Au2Sb16]4− anion is the first solid‐state all‐metal σ‐aromatic cluster with two 6‐σ‐electron aromatic fragments.